2012
DOI: 10.1111/cns.12043
|View full text |Cite
|
Sign up to set email alerts
|

Diammonium Glycyrrhizinate Attenuates Aβ1–42‐Induced Neuroinflammation and Regulates MAPK and NF‐κB Pathways In Vitro and In Vivo

Abstract: DG protects Aβ(1-42) -induced AD models in vitro and in vivo through reducing activation of microglia and inflammation, which may be involved in MAPK and NF-κB pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Among the kinases, MAPKs may be the key participators in the neurodegeneration seen in AD [22,23]. ERK and JNK, which are members of the MAPK superfamily, are closely associated with amyloid deposition and tau phosphorylation in AD and diabetes [24][25][26]. Liraglutide decreases inflammatory stress by inhibiting activation of JNK [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among the kinases, MAPKs may be the key participators in the neurodegeneration seen in AD [22,23]. ERK and JNK, which are members of the MAPK superfamily, are closely associated with amyloid deposition and tau phosphorylation in AD and diabetes [24][25][26]. Liraglutide decreases inflammatory stress by inhibiting activation of JNK [27].…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizic acid (GA), a triterpenoid saponin glycoside from the roots and rhizomes of licorice has been suggested to possess significant anti-inflammatory potential. Diammonium glycyrrhizinate (DG) (Table 1), the salt form of glycyrrhizin acid (GA), has been shown to inhibit Aβ 1–42 induced activation of p65 and MAPK signaling pathways in microglial cells and attenuate memory deficits in Aβ 1-42 induced AD in mice [78]. Xanthoceraside (Table 1), a triterpenoid saponin extracted from the husks of Xanthoceras sorbifolia Bunge has been shown to suppress MAPK and NF-κB signaling and inhibit the release of nitric oxide (NO) and pro-inflammatory cytokines in Aβ peptide induced microglial cells [79].…”
Section: Nf-κb As a Therapeutic Target For Neurodegenerative Diseasesmentioning
confidence: 99%
“…LPS binds mostly to toll-like receptor 4 (TLR4), a transmembrane receptor, consequently inducing intracellular signaling, which results in the activation of MAPKs and NF-jB signaling (Rousseau et al 2013). Interestingly, MAPKs including JNK, p38 and ERK1/2 have been described as the key regulators of proinflammatory cytokine production during inflammation induced by LPS (Zhao et al 2013). Recently it has been shown that microglia activation can also be governed by mechanisms involving caspase signaling.…”
Section: R E T R a C T E Dmentioning
confidence: 99%